2021
DOI: 10.1038/s41419-021-04421-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal long noncoding RNA HOXD-AS1 promotes prostate cancer metastasis via miR-361-5p/FOXM1 axis

Abstract: Development of distant metastasis is the main cause of deaths in prostate cancer (PCa) patients. Understanding the mechanism of PCa metastasis is of utmost importance to improve its prognosis. The role of exosomal long noncoding RNA (lncRNA) has been reported not yet fully understood in the metastasis of PCa. Here, we discovered an exosomal lncRNA HOXD-AS1 is upregulated in castration resistant prostate cancer (CRPC) cell line derived exosomes and serum exosomes from metastatic PCa patients, which correlated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 50 publications
(55 reference statements)
0
25
0
Order By: Relevance
“…Exosomal delivery of miR-26a inhibited metastasis and tumor growth in a PC mouse xenograft model [30]. Another report found that exosomal long lncRNA HOXD-AS1 was upregulated in the serum of patients with metastatic PC, suggesting that it may promote tumorigenesis by acting on the miR-361-5P/FOXM1 axis [31]. Collectively, these data reaffirm the possibility of developing tailored ncRNA therapeutics with reduced toxicity and improved specificity by exploiting recent innovations in chemical engineering.…”
Section: Noncoding Rna Therapeutics Approved By Regulatory Agenciesmentioning
confidence: 64%
“…Exosomal delivery of miR-26a inhibited metastasis and tumor growth in a PC mouse xenograft model [30]. Another report found that exosomal long lncRNA HOXD-AS1 was upregulated in the serum of patients with metastatic PC, suggesting that it may promote tumorigenesis by acting on the miR-361-5P/FOXM1 axis [31]. Collectively, these data reaffirm the possibility of developing tailored ncRNA therapeutics with reduced toxicity and improved specificity by exploiting recent innovations in chemical engineering.…”
Section: Noncoding Rna Therapeutics Approved By Regulatory Agenciesmentioning
confidence: 64%
“…The ceRNA hypothesis describes that lncRNAs, messenger RNAs, and transcribed pseudogenes compete for binding to miRNAs via miRNA response elements [ 29 ]. Several lncRNAs function as ceRNAs to facilitate or inhibit PCa progression [ 30 , 31 , 32 , 33 ]. In order to investigate whether RP11-1023L17.1 can function through sponge miRNAs, we hypothesized that miR-205-5p, miR-27b-3p, and miR-944 may sponge RP11-1023L17.1, but the correlation of their expression with RP11-1023L17.1 was relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…In several types of cancer, most lncRNAs are either up- or downregulated. These lncRNAs favor all stages of tumor development through the promotion of mRNA expression and constancy [ 253 ], by favoring mRNA stability [ 254 ], or by modulating miR [ 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 ]. The aberrant phenotype is the result of the modulation of typical pathways playing key roles in cell survival [ 255 , 259 , 263 , 265 , 283 ], apoptosis [ <...…”
Section: Analyzing Cernets For Diagnosis and Targeting Them For Thera...mentioning
confidence: 99%